2015
DOI: 10.5507/bp.2013.076
|View full text |Cite
|
Sign up to set email alerts
|

Chemical decellularization: a promising approach for preparation of extracellular matrix

Abstract: Background.A biological scaffold from extracellular matrix can be produced by a variety of decellularization methods whose caveat consists in efficiently eliminating cells from the treated tissue. This scaffold can be used in diverse applications for tissue engineering and organ regeneration. Preservation of the extracellular matrix ultrastructure is highly desirable because of its unique architecture, contained growth factors and decreased immunological response. All of these properties provide attachment sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 59 publications
1
41
0
1
Order By: Relevance
“…A removal of cells or nuclei was here confirmed by various microscope techniques, in accordance to other studies producing biological scaffolds (Crapo et al, ; Hrebikova, Diaz, & Mokry, ). However, our quantitative survey likewise resulted in a dramatic decrease of dsDNA in decellularized bovine cotyledons that was well within the established parameters of less than 50 ng dsDNA per mg of biological scaffold (Crapo et al, ; Hrebikova et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…A removal of cells or nuclei was here confirmed by various microscope techniques, in accordance to other studies producing biological scaffolds (Crapo et al, ; Hrebikova, Diaz, & Mokry, ). However, our quantitative survey likewise resulted in a dramatic decrease of dsDNA in decellularized bovine cotyledons that was well within the established parameters of less than 50 ng dsDNA per mg of biological scaffold (Crapo et al, ; Hrebikova et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Further loss of water-soluble GAGs occurred due to the process conducted in an aqueous solution which can easily wash away the separated GAGs from the tissues 44. According to Hrebíková, the chemical detergent SDS has a deleterious effect on the GAG content within the tissues 49. From the previous study, it revealed that GAG reduction after the decellularization process is a crucial step for future in vitro study.…”
Section: Discussionmentioning
confidence: 99%
“…Decellularized organ-derived extracellular matrix (dECM) has been used for many years in tissue engineering and regenerative medicine (Conklin et al, 2002;Dahl et al, 2003;Schenke-Layland et al, 2003). Decellularization of the extracellular matrix can be achieved through different physical, chemical or biological processes, including freeze/thaw cycles, use of organic detergents, and mild treatment with proteolytic enzymes (Crapo et al, 2011;Hrebikova et al, 2015;Keane et al, 2015;Leonel et al, 2017;Kawecki et al, 2018). Commonly, different processes are combined or used sequentially, so as to decrease the damage caused by each of them to the extracellular matrix but, at the same time, to potentiate the decellularization protocol (Crapo et al, 2011;Kawecki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%